Label-free isolation of lipid-rich Saccharomyces cerevisiae mutant by high-throughput flow-mode Raman-activated cell sorting and multi-omics analysis for uncovering the mechanism of enhanced lipid accumulation - Xiaotong Ji; Xixian Wang; Wenjun Zhou; Lin Chen; Tianzhong Liu; Jian Xu; Bo Ma (Biotechnology for Biofuels and Bioproducts)
Abstract Background Palmitoleic acid, a valuable functional fatty acid, is notably scarce in traditional oil crops, with the exception of certain wild plants such as macadamia nuts and sea buckthorn. Recently, the lipid from Saccharomyces cerevisiae was found to contain approximately 50% palmitoleic acid. Consequently, S. cerevisiae has the potential to sustainably produce palmitoleic acid through fermentation, provided that the issue of promoting its lipid content is addressed. Results In this work, based on the previously isolated oleaginous wild strain of S. cerevisiae, the mutagenesis by zeocin combined with ARTP was carried out to generate S. cerevisiae mutants, and then the high lipid content mutants were isolated using the flow-mode Raman-activated cell sorting (FlowRACS) technique, which allowed for the high-throughput selection of these mutants in a label-free and non-invasive manner. The mutant MU2R48 was finally obtained and its lipid content was 40.26%, 30.85% higher than the original type. Transcriptome and targeted metabolome analysis revealed a coordinated interaction of fatty acid precursor biosynthesis, the pentose phosphate pathway, ethanol degradation, and amino acid metabolism, synergistically channeling carbon flux from acetyl-CoA and NADPH into lipid biosynthesis. Additionally, key transcriptional regulators within the lipid metabolism network were implicated in this enhanced lipid accumulation. Conclusion In this study, a mutant strain of Saccharomyces cerevisiae MU2R48 with 40.26% lipid content was successfully generated through zeocin-ARTP mutagenesis combined with Raman-activated cell sorting. Multi-omics analysis revealed that the enhanced lipid accumulation was driven by coordinated up-regulation of precursor biosynthesis, carbon flux redirection, and key transcriptional regulators, with increased acetyl-CoA and NADPH production fluxes likely serving as the pivotal determinants.